PENGARUH LITERASI KEUANGAN DAN HARGA EMAS TERHADAP KEPUTUSAN INVESTASI EMAS PADA MASYARAKAT BANYONENG DAJAH - Sirrul Asrol Febriadi; Octaviana Arisinta (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2026)
This research aims to determine the influence of financial literacy and gold prices on gold investment decisions in the Banyoneng Dajah community. The type of research used is quantitative descriptive research. The data collection technique uses a questionnaire. For the validity of the instrument, validity and reliability tests are used, while the analysis methods used are normality test, partial hypothesis test (t test), and simultaneous hypothesis test (F test). Based on the partial hypothesis test (t test) of financial literacy that has been tested, the calculated t value is 3.031, while the significance value is 0.003 < 0.05, so it can be concluded that financial literacy influences gold investment decisions. Based on the partial hypothesis test (t test), the tested gold price obtained a calculated t value of 9.108, while the significance value was 0.000 < 0.05, so it can be concluded that the price of gold influences gold investment decisions. Based on partial hypothesis testing (F test), the calculated F value was 121.677 and the significance value was 0.000 < 0.05, so it can be concluded that financial literacy and gold prices simultaneously influence gold investment decisions)